STRATEGI PENGEMBANGAN JARINGAN INTERNET PADA DINAS KOMUNIKASI DAN INFORMATIKA KABUPATEN MERAUKE UNTUK OPTIMALISASI PELAYANAN PUBLIK - Maya Irawati; Aenal Fuad Adam; Syahrabudin Husein Enala (Papsel Journal of Humanities and Policy, 2025)
This research aims to analyze the strategies implemented by the Merauke Regency Communications and Information Service in developing internet networks to improve public services. This research uses qualitative research methods and a descriptive analysis approach. Data collection techniques are observation, interviews, and documentation, with data analysis techniques using data reduction, data presentation, and conclusion. The analysis results found that although there has been progress in developing internet networks, challenges such as limited infrastructure and access speed still need to be overcome. This research recommends that the Communications and Information Service continue to invest in infrastructure, strengthen collaboration with service providers, and improve educational programs for the community. In this way, optimization of public services can be achieved, providing significant benefits for the people of Merauke Regency. The research results show three main strategies implemented: core strategy, customer strategy, and cultural strategy. The core strategy focuses on improving network infrastructure and security, with efforts to expand network coverage in remote areas. The strategy emphasizes customer and assistance service provision. Meanwhile, the cultural strategy seeks to build pleasing cooperation between the Communications and Information Service and the community and increase digital literacy.